Challenges in Implementing Croatian Regional Policy within semi-European context - Zlatan Fröhlich; Irena Dokic (European Regional Science Association (ERSA), 2012)
Croatia is geographically, historically and culturally a part of the European territory. Regions, as specific units within a national territory, are defined differently on EU level than in Croatia, where counties are far too small to be considered as regions in EU terms. The implementation of European regional policy requires "comparability" of territories, which is done on the basis of the Nomenclature of Territorial Units for Statistics (NUTS). After long discussions with the European Commission and Eurostat, Croatia has three "new" NUTS II regions (March, 2007): Adriatic, North-Eastern (Pannonian) and North-Western Croatia including the capital city of Zagreb. These regions are now acceptable for EU regional policy and funds. Institutional structures for managing regional development on this new regional level does not exist, as well as legislative framework necessary to implement policies, strategies, plans or projects prepared at the respective levels, while at the same time very interesting developments from the bottom-up can be observed. Regional development agencies established have recently been nominated as regional coordinators for elaboration of planning documents at the County level initiating development processes, still at the county level and through informal mechanisms at the regional level. Territorial cohesion across Europe stands out as one of the top European priorities. Considerably large number of programmes, measures and priorities, aim at achievement of this goal. Croatia, as an acceding country, strives to harmonise numerous requirements prior to entering European union space in all aspects of entry, including territorial cohesion. Last decade was marked by a certain shift in shaping and implementing Croatian regional policy at programming and regulatory level towards that aim, among others. Many documents were produced – to serve national purpose, European and/or both. New policy, regulatory and programming environment imposed also creating of institutional set up (structure) that will enable successful implementation at all these fronts. However, regional development has to evolve from the bottom, but the initial push or supporting incentives have to come from above. This is a mutually enhancing development process, where efforts from above (EU and national level) and bellow (regions, counties, and local units) merge and contribute to overall development. This paper explores possibilities and obstacles in implementing of Croatian regional development policy at all levels, within a semi-European context and a given national framework.
Keywords: R00; R11; R58; 330; Croatian regional policy; regional development; competitiveness